2010
DOI: 10.1126/science.1174779
|View full text |Cite
|
Sign up to set email alerts
|

G Protein Subunit Gα 13 Binds to Integrin α IIb β 3 and Mediates Integrin “Outside-In” Signaling

Abstract: Integrins mediate cell adhesion to the extracellular matrix and transmit signals within the cell that stimulate cell spreading, retraction, migration, and proliferation. The mechanism of integrin outside-in signaling has been unclear. We found that the heterotrimeric guanine nucleotide-binding protein (G protein), Gα13, directly bound to the integrin β3 cytoplasmic domain, and that Gα13-integrin interaction was promoted by ligand binding to the integrin αIIbβ3 and by guanosine triphosphate (GTP)-loading of Gα1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
224
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 213 publications
(235 citation statements)
references
References 24 publications
9
224
2
Order By: Relevance
“…By generating mice in which the platelets were depleted of Gα 13 using siRNA 5 The confocal images very clearly showed that, in the absence of Gα 13 , platelets spread poorly on Fg, which was rescued by pretreatment with the Rho-kinase inhibitor Y27632, confirming previous findings that RhoA activated downstream of integrin α IIb β 3 inhibits platelet spreading. Interestingly, Gα 13 -depleted platelets failed to activate c-Src but accelerated RhoA activation.…”
supporting
confidence: 66%
See 2 more Smart Citations
“…By generating mice in which the platelets were depleted of Gα 13 using siRNA 5 The confocal images very clearly showed that, in the absence of Gα 13 , platelets spread poorly on Fg, which was rescued by pretreatment with the Rho-kinase inhibitor Y27632, confirming previous findings that RhoA activated downstream of integrin α IIb β 3 inhibits platelet spreading. Interestingly, Gα 13 -depleted platelets failed to activate c-Src but accelerated RhoA activation.…”
supporting
confidence: 66%
“…From these observations, the authors infer that Gα 13 is important for integrin-mediated c-Src activation and RhoA inhibition, leading to increased cell spreading. 5 Since Gα 13 regulates integrin-mediated cell spreading and c-Src activation, Gong et al examined the interaction of Gα 13 with α IIb β 3 using co-immunoprecipitation and GST pull-down assays. 5 They found that the GTP-bound form of Gα 13 shows enhanced interaction with the integrin β 3 subunit.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The Co-IP assay was performed as previously reported (53). Cell lysates from HLMVECs exposed to 1% O 2 or Fg4497 were incubated with either a mouse anti-tyrosine phosphorylation antibody, an anti-VE-cadherin antibody, or an equal amount of normal mouse or goat IgG, and then subsequently with protein A-or protein G-conjugated Sepharose beads, followed by Western blot (WB) analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Mammalian SLC3a2/4F2hc/CD98hc contributes to integrin outside-in signaling to regulate various integrin-mediated cell functions, including cell adhesion and cell-cell fusion (19,(21)(22)(23)(24). A downstream effector of integrin outside-in signaling is c-Src, which is phosphorylated at tyrosine 416 upon integrin-ligand binding (34). Because activation of c-Src transiently inhibits RhoA activity via p190RhoGAP (35), we hypothesized that zebrafish Slc3a2 might inhibit RhoA via c-Src activation.…”
Section: Slc3a2 Knockdown Enhances Plasma Membrane Fusion In the Ysl Andmentioning
confidence: 99%